Influence of CYP2D6, CYP3A5, ABCB1, APOE polymorphisms and nongenetic factors on donepezil treatment in patients with Alzheimer’s disease and vascular dementia - Yaowaluk T; Senanarong V; Limwongse C; Boonprasert R; Kijsanayotin P (Dove Medical Press, 2019)
Thitipon Yaowaluk1, Vorapun Senanarong2, Chanin Limwongse3, Rasda Boonprasert4, Pornpimol Kijsanayotin1 1Department of Pharmacology and Physiology, Faculty of Pharmaceutical Sciences, Chulalongkorn University, Bangkok, Thailand; 2Division of Neurology, Department of Medicine, Faculty of Medicine, Siriraj Hospital, Mahidol University, Bangkok, Thailand; 3Division of Medical Genetics, Department of Medicine, Faculty of Medicine, Siriraj Hospital, Mahidol University, Bangkok, Thailand; 4Clinical Toxicology Laboratory, Faculty of Medicine, Siriraj Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Pornpimol KijsanayotinDepartment of Pharmacology and Physiology, Faculty of Pharmaceutical Sciences, Chulalongkorn University, Phayathai Road., Pathumwan, Bangkok 10330, ThailandTel +66 2 218 8322Fax +66 2 218 8324Email pornpimol.k@chula.ac.thPurpose: This study aims to evaluate the influence of genetic polymorphisms of CYP2D6, CYP3A5, ABCB1, and APOE genes and nongenetic factors on steady-state plasma concentrations (Cpss) of donepezil and therapeutic outcomes in Thai patients with Alzheimer’s disease (AD) and vascular dementia (VAD).Patients and methods: Eighty-five dementia patients who received donepezil for at least six months were recruited. CYP2D6, CYP3A5, ABCB1, and APOE polymorphisms were genotyped. Cpss of donepezil was measured. Association of genetic and non-genetic factors with Cpss and clinical outcomes of donepezil (cognitive function as measured by the Thai Mental State Examination score; TMSE) were determined by using univariate and multivariate analysis.Results: Both univariate and multiple linear regression analysis indicated that only CYP2D6*10 allele was associated with higher Cpss (p-value =0.029 and B =0.478, p-value =0.032, respectively) that might influence the clinical outcomes of donepezil. ie, TMSE (p-value =0.010 and B =4.527, p-value =0.001) and ΔTMSE (p-value =0.023 and B =4.107, p-value =0.002), especially in patients with AD. Interestingly, concomitant use of memantine was found to be associated with increased Cpss of donepezil (p-value =0.007 and B =0.511, p-value =0.014). Whereas, co-medication with antidepressant drugs attenuated clinical responses in patients with AD (TMSE: B =−2.719, p-value =0.013 and ΔTMSE: B =−2.348, p-value =0.028). Age was a significant predictor of donepezil response in VAD patients. No significant association of CYP3A5*3, ABCB1 3435C>T or ABCB1 1236C>T, and APOE ϵ4 genotypes with Cpss or clinical outcomes of donepezil was found in this study.Conclusion: Our results suggests that CYP2D6*10 strongly influences Cpss and there is a trend toward better outcomes of donepezil in patients with AD. Nongenetic factors including concomitant drugs treatment might alter Cpss of donepezil or clinical outcomes.Keywords: donepezil, CYP2D6 polymorphisms, concomitant drugs treatment, Alzheimer’s disease, vascular dementia